The Development Of Tahara Web 2.0 Module For Secondary Schools In Pakistan - Zaibi, Dur E Najaf (2020)
The advent of Information and communication technology brought about enormous change in the teaching and learning patterns at various settings in Pakistan, yet the Islamic Studies subject at secondary level is far behind the intended plan in utilization of ICT in teaching and learning caused by self-accessing teaching strategies with minimal intervention necessitated this study. This led to the development of Tahara Web 2.0 module for the secondary schools in Pakistan.